Subdivision Graph, Power and Line Graph of a Soft Graph - Thumbakara, Rajesh K.; George, Bobin; Jose, Jinta (Communications in Mathematics and Applications, 2022)
Soft set is a classification of elements of the universe with respect to some given set of parameters. It is a new approach for modeling vagueness and uncertainty. The concept of soft graph is used to provide a parameterized point of view for graphs. In this paper we introduce the concepts of subdivision graph, power and line graph of a soft graph and investigate some of their properties.